Estimation of arm joint angular displacements in front crawl swimming using accelerometer - Ichikawa, H.; Ohgi, Y.; Miyaji, C.; Nomura, T. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to estimate arm joint angular displacements, such as shoulder extension and elbow flexion angle during front crawl swimming using an accelerometer that was attached to the swimmer's wrist. The arm joint angles were formulated and wrist acceleration was identified mathematically. A well-trained swimmer, as the subject, performed front crawl swimming with a wrist-mounted accelerometer. Shoulder extension and elbow flexion angle were estimated from the measured acceleration corresponding to the calculated acceleration. The estimated angles corresponded well with the angles obtained by videography. The desirable results demonstrated the possibilities of its practical use as a methodology to measure swimming motion.